Enterprise Architecture Planning Untuk Pengembangan Sistem Informasi Perguruan Tinggi - Khairina, Dyna Marisa; Mustafid, Mustafid; Noranita, Beta (JSINBIS (Jurnal Sistem Informasi Bisnis), 2012)
In the development of the information system needed a plan that will complement the university's strategic direction. Planning process utilizing enterprise architecture planning methodologies that produce a conceptual model of the enterprise architecture that includes data architecture, application and technology. This research aim to make enterprise architecture planning a conceptual model of the enterprise architecture as a high-level blueprint for data, applications and technology. Conceptual model enterprise architecture generated can be used as a blueprint for data, applications and technology in the development of information systems. Results of the blueprint enterprise became architecture planning for the needs of the data, estimates of technology platforms and applications as well as other things that are needed in the development of an integrated information system in university. Â  Keywords:Â  Enterprise architecture planning; Data architecture; Application architecture; Technology architecture